Comprehensive Study of the Microclimate Parameters in the Residential Building - Yurchenko, Yevhen; Kuznetsov, Valeriy; Radkevich, Anatolij V.; Koval, Olena; Skrzyniarz, Marek; Kruczek, Włodzimierz; Mike, Kamil; Mroczkowski, Łukasz (Sciendo, Poland, 2021)
ENG: The relevance of the research lies in the development of the current question about the influence of microclimate quality on the efficiency of residential units. The aim of the study is to examine how the microclimate parameters affect the efficiency of residential buildings. Findings. The results obtained are essential for the design of energyefficient and comfortable residential buildings. The scientific novelty and practical importance of research resides in the thorough study of microclimate in low-rise residential buildings. Microclimate deviation charts for residential buildings have been produced.
A. Radkevich: ORCID 0000-0001-6325-8517
Keywords: energy audit; heat-insulating cladding; heat insulation; energy efficiency; microclimate parameters; residential unit; complex thermal modernization; КБВ